Dominica : Poverty Reduction Strategy Paper; Preparation Status Report. (IMF Staff Country Reports; Country Report, 2005)
This paper discusses the Poverty Reduction Strategy Paper-Preparation Status Report for Dominica. The paper discusses that the government of the Commonwealth of Dominica has advanced its sectoral strategy to enhance growth in several dimensions. With technical assistance from the World Bank, the government has been reviewing its Electricity Supply Act to modify it and allow the exploitation of geothermal energy, which potentially can be exported to neighboring islands. The government has also made progress in the area of social protection.